Measurement of Carbon dioxide (CO2) Absorptive Capacity in a Secondary Amine based Aqueous Mixture: Experimental and Modelling Study - Ghulam Murshid; Shaima Al-Khayaria; Tan Lian See (Chemical Engineering Transactions, 2023)
Over the past 30 years, the increasing global temperature due to industrial emissions of greenhouse gases is considered as an immense threat to our environment which needs to be addressed. However, the number of industries has been increasing significantly over the past few decades, leading to the ever increasing emissions and worsening the air pollution situation. Carbon dioxide (CO2) is one of the major greenhouse gas contributing to the rapid climate changes and therefore, collective efforts are required to control its emissions. In this study, 20 experiments were conducted to study the solubility of CO2 in the mixture of two solvents diethanolamine and dimethylformamide (DEA and DMF). Design expert (DOE) software was used to design the solubility experiments in order to optimize the number of experiments and to develop a correlation between various variables such as temperature, pressure and solution concentration. The objective of this work was to measure the CO2 loading capacity in aqueous solutions of DEA and DMF at various operating conditions of temperature, pressure and solution concentrations. It was observed that by increasing the weight percent of DEA in the aqueous solution, solubility tends to increase. The maximum value of 0.7454 mol/mol of CO2 solubility was achieved at pressure of 8 bar and at temperature of 313.15 K which is found to be higher than the monoethanolamine (MEA). In addition to that important design property such as density was also measured at the wide range of temperature and concentrations. The new solubility and density data can be a useful contribution to design a better process to mitigate CO2 from various industrial streams.